Sustentabilidade no setor bancário brasileiro : a participação do banco Santander na elaboração do TEEB - Otoni, Suzanne Gomes (2014)
This dissertation focuses on the theme of sustainable development in the banking sector, highlighting the design and implementation of The Economics of Ecosystems and Biodiversity (TEEB) in its application in the brazilian banking sector. Systematizes the theoretical and conceptual framework on sustainable development highlighting the distinctions between traditional economics and ecological economics. Also systematizes the theoretical and conceptual background on environmental regulation, emphasizing their transition models of direct regulation, to the approaches of policy mix, especially for payments for environmental services (PES) and the TEEB. Thus, discusses sustainability initiatives in the banking sector in Brazil, highlighting the participation of Banco Santander in preparing the TEEB Brazil. Underscores how closing remarks that despite the progressive multiplication of sustainability initiatives in the banking sector, such processes are still incipient and persist uncertainties formatting specific regulation for the banking sector regarding the sustainability.